Microscopic observation of a liquid-liquid-(semi)solid phase in polluted PM2.5 - Gaikwad, Sanjit; Jeong, Rani; Kim, Dohyun; Lee, Kwangyul; Jang, Kyoung-Soon; Kim, Changhyuk; Song, Mijung (Frontiers in Environmental Science, 2022)
Atmospheric aerosol particles are complex mixtures having various physicochemical properties. To predict the role and characteristics of such complex aerosol particles in air pollution and related atmospheric chemistry, our knowledge of the number and types of phases in complex aerosol particles should be improved. However, most studies on the phase behavior of aerosol particles have been conducted in the laboratory and have not used real-world aerosol particles. In this study, using a combination of optical microscopy and poke-and-flow technique, we investigated the number and types of phases of actual aerosol particles of particulate matter < 2.5 µm (PM2.5) collected on heavily polluted days in Seosan, South Korea in winter 2020 – 2021. From the microscopic observations at 293 K, it showed that the PM2.5 particles exist in a single liquid phase at relative humidity (RH) > ~85%, a liquid-liquid phase at ~70% < RH < ~85 %, a liquid-liquid-(semi)solid phase at ~30% < RH < ~70%, and a (semi)solid phase at RH < ~30% upon dehydration. This reveals that three phases of atmospheric aerosol particles coexisting as liquid-liquid and liquid-liquid-(semi)solid would be the most common phases in the atmosphere considering ambient RH ranges. These observations provide fundamental properties necessary for improved predictions of air quality and aerosol chemistry such as reactive uptake of N2O5.